Impacts of COVID-19 Pandemic on Sleep Quality Evaluated by Wrist Actigraphy: A Systematic Review - Ferreira-Souza, Luiz Felipe; Julianelli-Peçanha, Marize; Coelho-Oliveira, Ana Carolina; da Silva Bahia, Christianne Martins Corrêa; Paineiras-Domingos, Laisa Liane; Reis-Silva, Aline; Moura-Fernandes, Márcia Cristina; Trindade-Gusmão, Luiza Carla; Taiar, Redha; da Cunha Sá-Caputo, Danubia; Rapin, Amandine; Bernardo-Filho, Mario (Journal of Clinical Medicine, 2023)
COVID-19 has probably contributed as a risk factor for sleep disturbance. Actigraphy has been used to evaluate sleep complaints in self-isolated populations and frontline doctors during the COVID-19 pandemic. This systematic review aims to summarize the impact of the COVID-19 pandemic on sleep through wrist actigraphy, estimating sleep latency, total sleep time, awakening-after-sleep onset, and sleep efficiency. Searches were conducted of observational studies on the PubMed, Embase, Scopus, Web of Science, and PEDro databases from 1 December 2019 to 31 December 2022. Ninety articles were found, and given the eligibility criteria, fifteen were selected. Six studies were classified by the National Health and Medical Research Council as evidence level IV, two studies as level III-3, and seven studies as level III-2. According to the ACROBAT-NRSI instrument, three studies were classified as having a “serious” risk of bias, two as having “critical” risk, four as having “moderate” risk, and six as having “low” risk. In the selected publications, various populations were evaluated via actigraphy during the COVID-19 pandemic, with reports of “poor” sleep quality. Actigraphy may be a relevant tool to assess individual day–night rhythms and provide recommendations under enduring pandemic conditions. Moreover, as actigraphy presents objective data for sleep evaluations, it is suggested that this method be used in similar pandemics and that actigraphy be included as part of the sleep hygiene strategy.
Keywords: COVID-19 pandemic; actigraphy; circadian rhythm; sleep; sleep schedules; social isolation